2005
DOI: 10.1111/j.1741-4520.2005.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences in cardiovascular anomalies induced by bis‐diamine between Sprague–Dawley and Wistar rats

Abstract: It is known that animals show different responses to the same teratogen between different strains. We examined cardiac malformations in Sprague-Dawley (SD) and Wistar rats induced by bis-diamine, which produced conotruncal anomalies and aortic arch malformations in embryos when administered to the dams, to elucidate the morphological differences and pathogenesis in the two strains. Two hundred milligrams of bis-diamine dissolved in 1% gum-tragacanth was administered to pregnant rats on embryonic day (ED) 9.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…WIN, having been briefly investigated as a potential male contraceptive (Heller et al, 1961), was shown to be a potent inducer of congenital heart defects including coronary defects, yet, the cause for such defects remains poorly understood (Oster et al, 1974; Kilburn et al, 1982; Binder, 1985; Tasaka et al, 1991; Ito et al, 1992; Okishima et al, 1992; Kuribayashi and Roberts, 1993; Jackson et al, 1995; Nishijima et al, 2000; Okamoto et al, 2004; Fujino et al, 2005; Kise et al, 2005; Hanato et al, 2011). We found that administration of WIN between E9.5 and E13.5 dramatically reduced the amount of RA and alters RA-signaling in developing mouse embryos and their hearts (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…WIN, having been briefly investigated as a potential male contraceptive (Heller et al, 1961), was shown to be a potent inducer of congenital heart defects including coronary defects, yet, the cause for such defects remains poorly understood (Oster et al, 1974; Kilburn et al, 1982; Binder, 1985; Tasaka et al, 1991; Ito et al, 1992; Okishima et al, 1992; Kuribayashi and Roberts, 1993; Jackson et al, 1995; Nishijima et al, 2000; Okamoto et al, 2004; Fujino et al, 2005; Kise et al, 2005; Hanato et al, 2011). We found that administration of WIN between E9.5 and E13.5 dramatically reduced the amount of RA and alters RA-signaling in developing mouse embryos and their hearts (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…NCC are essential to support normal heart morphogenesis [28][29][30][31] and alterations in the population, the developmental migration, or metabolism of NCC by surgical ablation, genetic deletion, or teratogenic insults lead to a panoply of cardiovascular defects [32][33][34][35][36][37][38]. Cardiac NCC originate from the lateral ridges of the neuroectoderm that span between the mid-otic placode and the caudal end of the third somite and contribute ectomesenchymal cells towards the development of the pharyngeal arches, the carotid, subclavian, innominate and coronary arteries, the aorticopulmonary septum, the conotruncal cushions, the distal portion of the ventricular septum, the walls of the ascending aorta, and the pulmonary trunk [28,29,39] and participate in the maturation of the cardiac conduction system [29,38,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…These are less extensive than those seen in rat fetuses with EA-TEF but are nevertheless frequent and severe. It is interesting that these defects are not induced only by nitrofen but also by other teratogens like bis-diamine [112,113] or benzofuranyl-ureas [114] that induce CDH and high proportions of facial, cardiovascular, thymic, and parathyroid malformations. This reveals that the malformative cluster is not specifically related to a particular teratogen but rather to dysmorphogenic mechanisms in which the NC signaling pathway is likely to be involved.…”
Section: Congenital Diaphragmatic Herniamentioning
confidence: 99%